Eschatology in the Quran: Charles Sanders Peirce's Semiotic Study of Surah Al-Waqi'ah - Ramadhan, Aji Rizqi; Arsyad, Hairuddin; Sopian, Asep; Fadlurrahman, Irsyad (Mashdar: Jurnal Studi Al-Qur'an dan Hadis, 2024)
This research aims to examine eschatological verses in Surah Al-Waqiah using Charles Sanders Peirce's semiotic theory, focusing on the relationship between the representamen (sign) and the object it represents. Peirce classified signs into three distinct categories: icon, index, and symbol. The study, conducted as library research using descriptive qualitative methods, employs content analysis for data interpretation. Upon analysis, it identifies eight verses featuring icons where the sign closely resembles the object it represents, such as depicting the universe's destruction as akin to the end of the world. It also identifies nine verses containing indices that clarify cause-and-effect relationships on the Day of Judgement, including the elevation or debasement of groups based on their worldly status and the consequences of indulgence and major sins leading to hellfire. Furthermore, 17 verses use symbols with conventional relationships, such as the "right" and "left" groups to represent categories of individuals in the afterlife and fruit-bearing trees representing perpetual pleasure in heaven. Peirce’s semiotics offers a new perspective for understanding the Quran's message concerning eschatological events that will occur on the Day of Judgement.